DIFFERENCES IN MORPHOLOGICAL CHARACTERISTICS BETWEEN JUNIOR BASKETBALL PLAYERS WHO HAVE DIFFERENT LEVELS OF EXPLOSIVE STRENGTH - Nedim Sisic; Damir Sekulic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: The aim of this study was to determine differences in morphological characteristics between junior basketball players who have different levels of explosive strength. Methods: The study was conducted on a sample of 84 junior basketball players from (B&H) Bosnia and Herzegovina (16-18 years) in spring 2013th. The sample of morphological variables consited of: body height, leg length, body weight, upper arm girth in extension, calf girth, triceps skinfold, abdominal skinfold, front thigh skinfold, BMI, the relative body fat percentage. The variables of explosive strength were: vertical jump (VJ), broad jump (BJ) and throwing a medicine ball from chest with 3 kg from a standing position. Ward's method of cluster analysis, based on variables of explosive strength we formed four homogeneous groups. Subsequently, using the ANOVA and post-hoc analysis, these groups are differentiated with regard to morphological characteristics. Results: Clusters differed significantly in BJ and VJ. ANOVA found significant differences between clusters in variables of skinfolds, such as the: triceps, abdomen and thigh. Discussion: Defined the influence of morphological variables on explosive strength can be regarded as expected, given that it is primarily about a negative influence of the amount of body fat on relative explosive strength type. This research has shown that junior basketball players in B&H are shorter and ligther when compared to top-level European juniors (Jelicic et al., 2002). Subjects with the lowest skinfolds of the upper limbs and body weight, achieved the best results in the manifestation of relative explosive strength, which has so far rarely been found in samples of trained subjects (Milanese et al., 2010). Possible explanations can be required in a number of training, the intensity and quality of training. Although at this point with certainty, we can't determine on which of these factors involved. This can be confirmed by the results of research of Piucco et al., 2009 who studied female amateur volleyball athltes. References: Jelicic M, Sekulic D, Marinovic M (2002). Coll. Antropol, 26, 69-76. Milanese C, Bortolami O, Bertucco M, Verlato G, Zancanaro C (2010). Journal of Human Sport and Exercise, 5(2), 265-79. Piucco T, Santos SG (2009). Fitness Performance Journal, 8(1), 9-15.